Novel Technique of Surgical Management of Scimitar Syndrome - Mary Lark; Amanda Cai; Phillip Rideout; David Gregg; Pal Suranyi; Fred A. Crawford; Valerian L. Fernandes (Case Reports in Cardiology)
Scimitar syndrome is a rare congenital abnormality resulting from right-sided pulmonary venous return to the inferior vena cava rather than to the left atrium. It is usually detected in early childhood with symptoms of recurrent chest infection and finding of pulmonary hypertension due to left to right shunt. We report a case of a 40-year-old woman with scimitar syndrome discovered on chest X-ray during evaluation of recurrent pneumonia. Surgical correction was achieved with a novel technique of using a synthetic graft connecting the scimitar vein across the right atrium to the left atrium along with ligation of the scimitar vein connection to the inferior vena cava. The patient continues to do well 10 years after surgery, and the shunt graft shows good flow on echocardiogram. We present her clinical and imaging data and details of the surgical technique along with a brief review of surgical literature.